Photovoltaic System Design, Feasibility and Financial Outcomes for Different Regions in Turkey - Kayhan, V. A.; Ulker, F.; Elma, O. (IEEE, 2015)
Energy is very important for countries which are developing rapidly, such as Turkey, during the fossil fuel prices are increasing. In this respect, renewable technologies such as PV systems are gaining importance in the world gradually due to its eco friendliness, easy applicability and increasing efficiency. Today, incentives for PV systems are being provided to private sector companies and people who would like to take benefit from generating energy from PV systems in Turkey. According to General Directorate on Renewable Energy (EIE), while the average annual sunshine and radiation are roundly 6.69 hour and 3.6 kWh/m(2)-day for Istanbul respectively, they are roundly 8.25 hour and 4.5 kWh/m(2)-day for Antalya. This paper makes an overview on PV systems and examines the financial outcome of PV system investment in Turkey. Two locations, Istanbul and Antalya, were taken into account in installing/constructing a PV Plant and these two systems were examined and compared in terms of their prices, feasibility, solar efficiencies regarding the location and future financial performances.
Keywords: Renewable Technologies; PV Systems; Solar Efficiency; Feasibility; Financial Performance; Energy & Fuels; Engineering